Thermal Tolerance in Anuran Embryos with Different Reproductive Modes: Relationship to Altitude - Manuel Hernando Bernal; John D. Lynch (The Scientific World Journal)
Anurans are ectothermic animals very sensitive to temperature, mainly during the embryonic stage. In addition, environmental temperature decreases with altitude, and the amphibian fauna changes. Therefore, we studied the relationship between the embryonic thermal tolerances of twelve species of anurans and the temperatures of their microhabitat along an altitudinal gradient from 430 m to 2600 m. We hypothesized that there is a strong thermal adjustment of embryos to their microhabitat and, consequently, that temperature could be a limiting factor of altitudinal distribution of the anurans. We also compared the embryonic thermal tolerances according to six postulated reproductive modes of the study species. We found a significant relationship between the maximum and minimum thermal tolerances of the anuran embryos and the maximum and minimum temperatures of their microhabitat and altitudinal distribution. We also found a wide range of embryonic thermal tolerances for aquatic breeding species and a narrower range for terrestrial breeding species. Particularly, embryos of direct development species were the most sensitive to temperature. These results show the strong thermal adjustment of anuran embryos to their microhabitat and elevation and do not reject the hypothesis that temperature can be a limiting factor of their altitudinal distribution.